2015
DOI: 10.3390/nu7075246
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid: A Hope for Alzheimer’s Disease Therapy from Plants

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by the deposition of extracellular amyloid-beta peptide (Aβ) and intracellular neurofibrillar tangles, associated with loss of neurons in the brain and consequent learning and memory deficits. Aβ is the major component of the senile plaques and is believed to play a central role in the development and progress of AD both in oligomer and fibril forms. Inhibition of the formation of Aβ fibrils as well as the destabilization of preformed Aβ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
137
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(140 citation statements)
references
References 93 publications
2
137
0
1
Order By: Relevance
“…Nowadays, it has been approved beneficial for a variety of serious chronic diseases, such as intestinal ischemia (Huang, 2015), cancer (Serafim et al, 2011), cardiovascular disease (Ardiansyah et al, 2008), skin diseases (Lin et al, 2005), diabetes (Jung et al, 2007), cochlea oxidative damage caused by repeated noise exposure (Fetoni et al, 2013), and oxidative stress of human dermal fibroblasts (Calabrese et al, 2008). In addition, the free radical scavenging activity of FA can relieve a variety of neurodegenerative disease, especially Alzheimer's disease (Sgarbossa et al, 2015;Sultana, 2012). It was reported that FA reverted oxidative stress induced by Abeta in LAN5 neuronal cells (Picone et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it has been approved beneficial for a variety of serious chronic diseases, such as intestinal ischemia (Huang, 2015), cancer (Serafim et al, 2011), cardiovascular disease (Ardiansyah et al, 2008), skin diseases (Lin et al, 2005), diabetes (Jung et al, 2007), cochlea oxidative damage caused by repeated noise exposure (Fetoni et al, 2013), and oxidative stress of human dermal fibroblasts (Calabrese et al, 2008). In addition, the free radical scavenging activity of FA can relieve a variety of neurodegenerative disease, especially Alzheimer's disease (Sgarbossa et al, 2015;Sultana, 2012). It was reported that FA reverted oxidative stress induced by Abeta in LAN5 neuronal cells (Picone et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, ferulic acid has antioxidant and anticancer properties131415. Ferulic acid has been shown to impart beneficial effects in diabetes, Alzheimer's disease, and cardiovascular disease by regulating antioxidant enzyme and caspase activities, COX-2, and hypertension161718. In the skin, ferulic acid has been shown to have a protective effect on UVB-induced erythema19.…”
Section: Introductionmentioning
confidence: 99%
“…into 4-vinylguaiacol and hydroferulic acid [76]. Further breakdown converts these products into the caffeic and vanillic acid, which have potent therapeutic effects especially in Alzheimer’s disease (AD) [77]. Soya-ioflavone daidzein is converted exclusively in equol only by Adlercreutiza equolifaciens, giving it a greater pro-estrogenic effect [78] Furthermore, the conversion of ellagic acid into urolithin is conducted by Gordonibacter urolithinfaciens; however the accumulation of the variety of biotransformaion products was dependent on the presence of the complex microbiota [79].…”
Section: The Identification Of Bacteria Capable Of Converting Polyphementioning
confidence: 99%